Prototipe Alat Monitoring Suhu dan Sistem Kontrol pada Trainer Refrigerasi Berbasis Raspberry Pi 3 B+ - Arman, Muhammad; Ayu, Wirenda Sekar; Sugiyarto, Sugiyarto; Pratikto, Pratikto; Hakim, Kamal Amrizal; Sandra, Dinara Safina; Syarief, Eliana (Jurnal Otomasi Kontrol dan Instrumentasi, 2024)
A refrigeration trainer is a working model of an existing system intended to support student learning in the characterization of refrigeration systems, especially their temperature profile. There are many ways to monitor temperature in refrigeration trainers, such as by implementing a temperature monitoring and control system based on Raspberry Pi 3 B +. This project uses the DS18B20 sensor and Raspberry Pi 3 B+ microprocessor. This system has various features such as temperature monitoring, on/off control for fans and compressors, online and offline data storage, and remote control. After 4 hours of testing, the prototype looked stable without any sudden increase or decrease in temperature values for all measurement point parameters. In addition, the error percentage value which is less than 10% shows that the DS18B20 temperature sensor used provides the best accuracy value and is considered adequate for this prototype.